Aspergillus flavus POPULATION AND AFLATOXIN B1 CONTENT OF PROCESSED PEANUT PRODUCTS IN MUNICIPALITY OF BOGOR, WEST JAVA, INDONESIA - Okky Setyawati Dharmaputra; Santi Ambarwati; Ina Retnowati; Amanda Windyarani (SEAMEO BIOTROP, 2013)
The objectives of this study were to get informations on the population of A. flavus and aflatoxin B1 content of five processed peanut products collected from retailers in Kecamatan Bogor Tengah (Subdistrict of Central Bogor), Municipality of Bogor. A total of 129 samples of processed peanut products was collected. They consisted of roasted peanuts with skin pods (33 samples), flour-coated peanuts (33), siomay sauce (18), pecel/gado-gado sauce (33) and satai sauce (12). A sample each of 2 000 g roasted peanuts with skin pods as well as flour-coated peanuts, and a sample each of 1 500 g siomay sauce, pecel/gado-gado sauce as well as satai sauce was mixed homogenously. It was then divided two times manually to obtain working samples to determine A. flavus population, AFB1 content and a reserve sample. Peanut kernels of roasted peanuts with skin pods and flour-coated peanuts were obtained by peeling their skin pods and the batter coat of tapioca flour manually, respectively. Aspergillus flavus in peanut processed products was isolated using a serial dilution method, followed by pour plate method on Aspergillus Flavus and Parasiticus Agar (AFPA). AFB1 content was determined using Thin Layer Chromatography method. Two replicates were used for each sample. The results showed that the population of A. flavus in roasted peanuts with skin pods, flour-coated peanuts, siomay sauce, pecel/gado-gado sauce and satai sauce were 0.3, 0.1, 0.3, 13.2 and 0.4 cfu/g (wet basis), respectively. The highest AFB1 content ofÂ processed peanut products (43.2 ppb) was found in roasted peanuts with skin pods, followed by flour-coated peanuts (34.3 ppb), satai sauce (23.2 ppb), pecel/gado-gado sauce (17.1 ppb) and siomay sauce (4.4 ppb).